2017
DOI: 10.1002/ep.12705
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of the combustion behavior of energy grass and three other types of biomass upon lignocellulosic composition

Abstract: The combustion characteristics of four kinds of biomass fuels (energy grass, sawdust, corn cob, and walnut shell) are investigated in this article. All the samples are heated from room temperature to 800°C at multiple heating rates of 10, 20, and 30°C/min. The effect of hemicellulose, cellulose, and lignin components on the pyrolysis and combustion processes of energy grass is explored by comparison to those of the other three types of biomass. The hemicellulose and cellulose content of samples could improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The positive effect of Cel on the combustion performance index seems to be in disagreement with the results by Pang et al, 15 who reported a decrease in combustion reactivity for chars produced from some cellulose-rich biomass sources. Nevertheless, Ma et al 46 observed that biomass sources having relatively low cellulose to lignin content ratios exhibited poorer combustion performances. In accordance with the argument made by Yan et al, 17 a relatively low content of lignin could result in a lower insulation of cellulose, which could then easily decompose and lead to chars with enhanced ignition characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…The positive effect of Cel on the combustion performance index seems to be in disagreement with the results by Pang et al, 15 who reported a decrease in combustion reactivity for chars produced from some cellulose-rich biomass sources. Nevertheless, Ma et al 46 observed that biomass sources having relatively low cellulose to lignin content ratios exhibited poorer combustion performances. In accordance with the argument made by Yan et al, 17 a relatively low content of lignin could result in a lower insulation of cellulose, which could then easily decompose and lead to chars with enhanced ignition characteristics.…”
Section: Resultsmentioning
confidence: 99%